CODE – MIXING IN ENGLISH CLASSES OF SMPN 14 KOTA BENGKULU: VIEWS FROM THE TEACHERS - Tri Ramadhaniarti; Safnil Arsyad; Arono Arono (Universitas Bengkulu, 2017)
English teachers in all levels of education in Indonesia try hard to make their students able to speak and write English. Teachers sometimes use code-mixing in their classroom instructions. This study is conducted to investigate Code – Mixing in English Classes of SMPN 14 Kota Bengkulu: Views From the Teachers. The participants were the English teachers who teach English at SMPN 14 Kota Bengkulu. The data were collected from audio-recording and interviewing to the teachers. The results indicated that teachers used inter-sentential code-mixing more frequently than intra-sentential code-mixing. It also found that all of the teachers used code-mixing in pre-activity, while activity and post-activity of teaching and learning process in their English classes. They also used code-mixing for giving instruction, translation and asking for clarification. The English-Indonesian pattern is the most frequently used by the teachers in teaching English. The teachers used code-mixing in teaching English in the English classes to make the students able to understand the purpose of teaching and learning process easily.